The Role of Information Technology in Supporting Transparency and Accountability of Village Government in Tongke-Tongke Village - Salman, Salman; Abd.Wahid; Mukrimah, Mukrimah; Erwin Sykuri; Sofyang, Sofyang (Tinta Emas Institute, 2025)
Bureaucratic reform at the village level is a strategic step to enhance transparency and accountability in governance. This study aims to analyze the role of information technology in supporting transparent and accountable governance in Tongke-Tongke Village. Using a descriptive qualitative approach, the research involved observations, surveys, and documentation to collect data from village officials, the community, and external policies. The findings reveal that the implementation of information technology, such as official websites and Android-based applications, has successfully improved administrative efficiency, strengthened information openness, and enabled active community participation in decision-making processes. Additionally, digitally documented village financial reports allow the community to monitor budget management in real-time. However, key challenges include low digital literacy and limited internet infrastructure. Through regular training and collaboration with internet service providers, Tongke-Tongke Village demonstrates its commitment to creating better governance. This study concludes that information technology can serve as a key catalyst for accelerating bureaucratic reform at the village level.